The Tristan Chord Resolved - Martin, Nathan (Intersections, 2008)
AbstractA little-noticed passage from Moritz Hauptmann’s 1853 treatise Die Natur der Harmonik und der Metrik very nearly describes the opening progression of Wagner’s Tristan. The present paper surveys the various analyses of the Tristan chord presented in the theoretical literature and defends an analysis derived from Hauptmann as a viable alternative.